Information System of Blood Needs Stock on The Indonesian Red Cross Using Weighted Moving Average Method - Rakhman, Arif; Sabanise, Yerry Febrian (SENATIK STT Adisutjipto, 2019)
The Indonesian Red Cross (PMI) is a national national association organization in Indonesia engaged in the field of social, humanitarian and health. The logistics section of the Blood Transfusion Unit (UTD) is a warehouse where blood stock is store in, out, or destroyed blood. The importance of blood availability at requires The Indonesian Red Cross requires The Indonesian Red Cross to always maintain the availaibility of blood to meet the need for blood tranfusion . the application of prediction as an effort to control blood supply is considered important. This is needed to minimize the amount of ordering and storing blood that must be borne by The Indonesian Red Cross. For this reson, a precise prediction method is needed in order to produce an accurate estimate of blood supply. In this study the prediction of blood is done using the Weigthed Moving Average (WMA) method, because the patern of stock data and blood demand owned by The Indonesian Red Cross follows the trend data pattern. Comparison of the smallest error value between the 3th-month WMA period and 6th-month  WMA selected to be the result of focasting. The results of the average error value (MAD, MSE, and MAPE) show a period of 6 months has the smallest value, although there is a decline in blood type AB, but the difference in the ratio of error values in goldar AB is not too far. This happens because donors or requests for AB goldar are not too many.